2008
DOI: 10.1159/000113421
|View full text |Cite
|
Sign up to set email alerts
|

The Rare Association of Truncus Arteriosus with a Cervical Double Aortic Arch Presenting with Left Main Bronchial Compression

Abstract: Truncus arteriosus, a double aortic arch, and a cervical aortic arch are all rare cardiovascular anomalies. We experienced a unique female newborn with the rare combination of truncus arteriosus with a cervical double aortic arch, which probably resulted from abnormal persistence of the bilateral 2nd or 3rd rather than the 4thembryonic aortic arches and failure of regression of the right 8th somitic segment of the right dorsal aorta. She presented with respiratory distress soon after birth, which was initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Patent foramen ovale is frequent, atrial septal defect is observed with about 10 % of the cases. Also atrioventricular discordance, situs inversus with dextrocardia, double inlet ventricle, atrioventricular valve stenosis and atresia, hypoplastic left ventricle, atrioventricular canal defect, vascular ring may be accompanied 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Patent foramen ovale is frequent, atrial septal defect is observed with about 10 % of the cases. Also atrioventricular discordance, situs inversus with dextrocardia, double inlet ventricle, atrioventricular valve stenosis and atresia, hypoplastic left ventricle, atrioventricular canal defect, vascular ring may be accompanied 10 .…”
Section: Discussionmentioning
confidence: 99%
“…We report the 10th known case of common arterial trunk with double aortic arch, and the first in utero diagnosis in the literature . Other reported cases have presented with respiratory symptoms of a vascular ring, which most commonly include respiratory distress and even respiratory arrest in infants.…”
Section: Introductionmentioning
confidence: 87%
“…Common arterial trunk (CAT) is a rare congenital malformation characterized by a single arterial trunk arising from the heart, overriding the interventricular septum and gives rise to the systemic, pulmonary, and coronary circulations 1 . The incidence of defect is 6-10/100,000 live births, it is occasionally associated with aortic arch anomaly such as right aortic arch and aortic arch interruption 1,2 . Double aortic arch (DAA) is the most common vascular ring, and results from persistence of both 4 th arches, compressing the trachea or esophagus or both 2 .…”
Section: Introductionmentioning
confidence: 99%